BASIC TENDENCIES OF THE DEVELOPMENT OF THE PRIMARY HEALTH CARE AND THE STRATEGIES OF THE PROTECTION OF THE MOTHERHOOD AND CHILDHOOD. (Conference Zone, 2022)
This article presented the new reformations on medical field primary medical-sanitation aid which is conducting by our current president in order to develop the system and improve people's life having to utilize state health care. The whole moderated configurations are based on the great purpose which our medical system can be competed with world health care standards, not only our citizens, even though it is bound to be the professional health centers where available to have the latest and most efficient therapies for foreign countries' people who need qualified care, as if in the past our land would be the Medical centers for among foreign countries